2021
DOI: 10.1002/art.41589
|View full text |Cite
|
Sign up to set email alerts
|

Etanercept or Methotrexate Withdrawal in Rheumatoid Arthritis Patients in Sustained Remission

Abstract: Objective. Patients with rheumatoid arthritis (RA) in whom remission is achieved following combination therapy with methotrexate plus etanercept face an ongoing medication burden. This study was undertaken to investigate whether sustained remission achieved on combination therapy can be maintained with either methotrexate or etan ercept monotherapy, as assessed following discontinuation of one or the other medication from the combination.Methods. Of the 371 adult patients with RA who received combination thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
38
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 34 publications
0
38
1
Order By: Relevance
“…After excluding duplicates and irrelevant articles, 211 full-text articles were assessed for eligibility. By reading full-text, 72 articles met the inclusive criteria and exclusive criteria ( 11 – 82 ). The following diagram of the study selection process for this meta-analysis is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After excluding duplicates and irrelevant articles, 211 full-text articles were assessed for eligibility. By reading full-text, 72 articles met the inclusive criteria and exclusive criteria ( 11 – 82 ). The following diagram of the study selection process for this meta-analysis is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…40 articles ( 12 , 15 , 17 , 22 , 25 28 , 30 , 31 , 33 , 34 , 36 , 38 , 40 42 , 45 , 49 , 54 56 , 58 60 , 62 66 , 72 77 , 79 82 ) reported the occurrence of AEs and 15285 RA patients was included. The network of eligible comparisons was shown in the Supplementary Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a few matters need to be addressed.First, the eligibility criteria state that patients should have an SDAI score of ≤3.3 at screening and at the end of the run-in period. However, Curtis and colleagues report that disease in 95%, 92.1%, and 96.1% of the patients in the methotrexate monotherapy arm, the etanercept monotherapy arm, and the combination arm, respectively, was in SDAI-defined remission at baseline (see Table 1 in Curtis et al [1]). Considering the eligibility criteria, these values should be 100% in each arm.Second, we noticed the discrepancy between the percentage of patients at baseline whose disease was in SDAI-defined remission (>90%) as compared to Boolean-defined remission (33-45%).…”
mentioning
confidence: 99%
“…Reducing medication exposure will help reduce the development of side effects and complications, especially with an aging population with polypharmacy concerns and complications. The authors of a recent article published in Arthritis & Rheumatology titled “Etanercept or Methotrexate Withdrawal in Rheumatoid Arthritis Patients in Sustained Remission.” help explore this idea of medication withdrawal through the Study of Etanercept and Methotrexate in Combination or as Monotherapy in Subjects with Rheumatoid Arthritis (SEAM‐RA) clinic trial and database ( 1 ).…”
mentioning
confidence: 99%